Effect of surface ligands on gold nanocatalysts for CO2 reduction. Issue 45 (2nd November 2020) - Shang, Hongyu; Wallentine, Spencer K.; Hofmann, Daniel M.; Zhu, Quansong; Murphy, Catherine J.; Baker, L. Robert
Abstract : Dodecanethiol on Au nanoparticles significantly enhances selectivity and stability with minimal loss in activity by acting as a CO2 -permeable membrane, which blocks the deposition of metal ions that are otherwise responsible for rapid deactivation. Abstract : Nanoparticle catalysts display optimal mass activity due to their high surface to volume ratio and tunable size and structure. However, control of nanoparticle size requires the presence of surface ligands, which significantly influence catalytic performance. In this work, we investigate the effect of dodecanethiol on the activity, selectivity, and stability of Au nanoparticles for electrochemical carbon dioxide reduction (CO2 R). Results show that dodecanethiol on Au nanoparticles significantly enhances selectivity and stability with minimal loss in activity by acting as a CO2 -permeable membrane, which blocks the deposition of metal ions that are otherwise responsible for rapid deactivation. Although dodecanethiol occupies 90% or more of the electrochemical active surface area, it has a negligible effect on the partial current density to CO, indicating that it specifically does not block the active sites responsible for CO2 R. Further, by preventing trace ion deposition, dodecanethiol stabilizes CO production on Au nanoparticles under conditions where CO2 R selectivity on polycrystalline Au rapidly decays to zero. Comparison with other surface ligands and nanoparticles shows that this effect is specific to both the chemical identity and the surface structure of the dodecanethiol monolayer. To demonstrate the potential of this catalyst, CO2 R was performed in electrolyte prepared from ambient river water, and dodecanethiol-capped Au nanoparticles produce more than 100 times higher CO yield compared to clean polycrystalline Au at identical potential and similar current.